Return of Ethics into Business Activities – From Utilitarianism to Conscious Consumers (review) - Tóth, Eszter (International Journal of Engineering and Management Sciences, 2019)
According to the common understanding of economic science people following their own preferences looking for ractional decisions which might bring the biggest advantage available. General economic models take this pre-condition as an axiom, however while analysing real processes and motivation, human side, ethics and values cannot be ignored. Business ethics has always been part of economics though having a diminishing role occasionally. Current developing movements of conscious consumers reveal the importance of the topic, highlighting personal creed and moral principles. Analytical frameworks incorporating ethical considerations are albeit more complicated hence offer more realistic interpretation of economic activities and therefore practical benefits at the end. Our study is a general review on this phenomenon.